(untitled) (DIGITAL TRANSFORMATION AND ARTIFICIAL INTELLIGENCE, 2025)
The work developed a mathematical model and a numerical algorithm for monitoring and forecasting the process of the spread of harmful substances in the atmosphere, taking into account the change in the movement of particles in the atmosphere. A detailed analysis of the developed mathematical models and numerical algorithms related to the processes of transport and diffusion of harmful substances in the atmosphere was carried out.